Morphological supply in response to systemic demand: the Greek past iteratives from birth to death - Willi, A (Buske, 2025)
The Homeric past iteratives in -σκε/ο- have been the object of much discussion, notably with regard to their Indo-European background and the question whether their creation is due to language contact with Anatolian, where the Hittite formations in -ške- seem to play a somewhat similar semantic role. In this article, the focus is shifted towards an exploration of the functional placement of the type within the verbal system of early Greek and its relationship with other tense-aspect categories. After a brief overview of the principal semantic values attached to the past iteratives, it is argued that they may best be conceptualized as originating from imperfectivized perfectives. As such they counterbalanced the emergence of perfectivized imperfectives, realized as augmented imperfects, in a four-slot system that resembles the one found in the synthetic past tenses of Modern Bulgarian. Following the repurposing of the augment as a universal past-tense marker and the extension of the -σκε/ο- suffix also to imperfective bases, this four-slot system lost its previous equilibrium and this led to the replacement of the morphological expression of past iterativity by the syntactic alternative construction of classical Greek.